2007
DOI: 10.1007/s00467-006-0289-x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal peritonitis in children on peritoneal dialysis

Abstract: Fungal peritonitis is a rare but serious complication in children on peritoneal dialysis (PD). In this study, risk factors were evaluated, and therapeutic measures were reviewed. A retrospective, multi-centre study was performed in 159 Dutch paediatric PD patients, between 1980 and 2005 (3,573 months). All peritonitis episodes were reviewed. Fungal peritonitis episodes were evaluated based on possible risk factors and treatment strategy. A total of 321 episodes of peritonitis occurred, with 9 cases of fungal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
1
28
3
2
Order By: Relevance
“…The reported prevalence of FP was 2% of all peritonitis episodes in data collected by the IPPR and 2.9% in a pediatric Dutch study (125,4). Recent data in adults reveal rates of 1.5% -5.8% (126).…”
Section: Rationalementioning
confidence: 91%
See 1 more Smart Citation
“…The reported prevalence of FP was 2% of all peritonitis episodes in data collected by the IPPR and 2.9% in a pediatric Dutch study (125,4). Recent data in adults reveal rates of 1.5% -5.8% (126).…”
Section: Rationalementioning
confidence: 91%
“…Observational studies suggest that frequent peritonitis, particularly episodes with gram-negative organisms, recent antibiotic therapy, and immunosuppression, can all be risk factors for FP in adults and in children (125,(127)(128)(129)(130). Warady et al (130) found that 56% of children with FP had received antibiotics in the preceding month, half of them for bacterial peritonitis.…”
Section: Rationalementioning
confidence: 99%
“…Intraabdominal candidaisis (IAC) results from entry of C. albicans into the abdominal cavity through translocation across the GI mucosal barrier or by direct inoculation, which can occur via contaminated peritoneal dialysis catheters or as a result of perforation of the GI tract (85)(86)(87)(88) (Fig. 2C).…”
Section: Non-cd4mentioning
confidence: 99%
“…Candida species are the most common fungi isolated (6,26,27). Peritonitis due to various filamentous fungi is also reported.…”
Section: Case Reportmentioning
confidence: 99%